2001
DOI: 10.1161/01.cir.103.4.597
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Inhibit Flow-Induced Smooth Muscle Cell Migration

Abstract: Flow-induced EC PAI-1 inhibits flow-induced SMC migration in vitro. EC PAI-1 expression may be one of the predominant mechanisms responsible for controlling the process of vascular remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 35 publications
3
65
2
Order By: Relevance
“…Our results are consistent with observations in diverse systems and with diverse cell types (O'Grady et al 1981;Saksela and Rifkin 1988;Clowes et al 1990;Redmond et al 2001;Jackson and Reidy 1992;Bendeck et al 1994;Stefansson and Lawrence 1996;Werb et al 1997). Migration of human VSMC in vitro has been shown previously to be decreased by PAI-1 (Stefansson and Lawrence 1996;Redmond et al 2001).…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with observations in diverse systems and with diverse cell types (O'Grady et al 1981;Saksela and Rifkin 1988;Clowes et al 1990;Redmond et al 2001;Jackson and Reidy 1992;Bendeck et al 1994;Stefansson and Lawrence 1996;Werb et al 1997). Migration of human VSMC in vitro has been shown previously to be decreased by PAI-1 (Stefansson and Lawrence 1996;Redmond et al 2001).…”
Section: Figuresupporting
confidence: 92%
“…Migration of human VSMC in vitro has been shown previously to be decreased by PAI-1 (Stefansson and Lawrence 1996;Redmond et al 2001). Administration of a plasmin inhibitor, tranexamic acid, suppressed VSMC migration after injury of rat carotid arteries (Jackson and Reidy 1992).…”
Section: Figurementioning
confidence: 85%
“…Coculturing of HUVEC in transwells inserted in a 24-well plate with confluent monolayers of SMC is a basic model of vascular wall, which has been demonstrated in other previous studies. 7,9,10,11,21 In the present study, SMC proliferation and migration of SMC to the endothelial cell layer 1 could not be demonstrated in our short time of investigation. The previous study in saphenous vein culture demonstrated TNF-regulated SMC proliferation and migration within 7 days.…”
Section: Discussioncontrasting
confidence: 64%
“…To date, no in vitro vascular model has been demonstrated for pharmacological studies in atherosclerosis, even though there have been several studies with other vascular diseases. [9][10][11] In the present study, we first constructed the in vitro model vascular wall with endothelial cell dysfunction in eNOS production by TNF-to mimic the important basic early stage pathology of atherosclerosis, and determined the potential of the model by using E2 as an antiatheroslerogenic agent. …”
mentioning
confidence: 99%
“…Oscillatory shear stress induces VSMC migration by increasing the expression of MMP-2 and MMP-9 and decreasing plasminogen activator inhibitor-1 (PAI-1) expression [134,135]. In vascular grafts, disturbed flow provides favourable conditions for VSMC proliferation with low shear stress, which may explain, in part, why intimal hyperplasia and atherosclerotic lesions develop preferentially in slow-flow regions [136].…”
mentioning
confidence: 99%